2018
DOI: 10.1089/cap.2017.0096
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting Injectable Atypical Antipsychotic Use in Adolescents: An Observational Study

Abstract: Our clinical experience suggests that SG-LAIAs may be a safe treatment option during adolescence in inpatients with psychotic disorders, as well as with DBD. No differences were found in CGAS improvement scores between the three SGA-LAIAs used, although patients on risperidone reported more side effects than those on aripiprazole. Further research is needed so as to evaluate safety and effectiveness of SG-LAIAs in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…A mean improvement of 31.7 (SD = 8.7) between admission and discharge was observed on the Children's Global Assessment Scale (CGAS); no differences were found between the different LAIs. Although they were generally well tolerated, 23.3% of patients reported mild short-term side effects, which were more frequent with risperidone than with aripiprazole (p = 0.014) (82).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A mean improvement of 31.7 (SD = 8.7) between admission and discharge was observed on the Children's Global Assessment Scale (CGAS); no differences were found between the different LAIs. Although they were generally well tolerated, 23.3% of patients reported mild short-term side effects, which were more frequent with risperidone than with aripiprazole (p = 0.014) (82).…”
Section: Discussionmentioning
confidence: 93%
“…An observational retrospective study (82) focused on the use of second-generation LAIs in adolescence. The use of risperidone (36.7%), aripiprazole (40%), and paliperidone palmitate (23.3%) LAI was mainly based on a history of low compliance (90%) and/ or poor insight (73.3%).…”
Section: Discussionmentioning
confidence: 99%
“…We propose that LAI‐AP should be introduced as early as possible in FEP‐SUD subjects, since this population represents a great challenge for treatment adherence and response. Further studies will be necessary to fully understand the clinical, functional and pharmacoeconomical impacts of this strategy, as some recent studies have already shown in general cohorts (Collins et al, ; Fortea et al, ; Lefebvre et al, ; Stip & Lachaine, ).…”
Section: Resultsmentioning
confidence: 99%
“…Long-acting injectable antipsychotics (LAIAs) may provide an ideal solution to this problem. A recent observational study of LAIAs (specifically: aripiprazole, risperidone, and paliperidone) in hospitalized adolescents with mental illness suggest that LAIAs are well tolerated and associated with improvements in the Children's Global Assessment Scale (CGAS) (Fortea et al, 2018). While there are no studies looking at LAIAs in youth with ASD specifically, outside of a single case report (Kowalski et al, 2011), work in other psychiatric disorders such as schizophrenia suggest that they are safe and well tolerated, with similar side effect profiles to oral medications.…”
Section: Long Acting Injectable Antipsychoticsmentioning
confidence: 99%